2016
DOI: 10.1038/srep19954
|View full text |Cite
|
Sign up to set email alerts
|

X-ray induced singlet oxygen generation by nanoparticle-photosensitizer conjugates for photodynamic therapy: determination of singlet oxygen quantum yield

Abstract: Singlet oxygen is a primary cytotoxic agent in photodynamic therapy. We show that CeF3 nanoparticles, pure as well as conjugated through electrostatic interaction with the photosensitizer verteporfin, are able to generate singlet oxygen as a result of UV light and 8 keV X-ray irradiation. The X-ray stimulated singlet oxygen quantum yield was determined to be 0.79 ± 0.05 for the conjugate with 31 verteporfin molecules per CeF3 nanoparticle, the highest conjugation level used. From this result we estimate the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 47 publications
1
96
0
4
Order By: Relevance
“…135 The results showed that the quantum yield of X-ray induced 1 O 2 generation was 0.79 ± 0.05 for the most efficient conjugate with 31 VP molecules per nanoparticle. This conjugate converts 1 O 2 molecules at the level of 1.2 × 10 8 to 2.0 × 10 9 per cell upon exposure to high energy (6 MeV) radiation with a radiotherapeutic dose of 60 Gy.…”
Section: Depth Penetrationmentioning
confidence: 97%
“…135 The results showed that the quantum yield of X-ray induced 1 O 2 generation was 0.79 ± 0.05 for the most efficient conjugate with 31 VP molecules per nanoparticle. This conjugate converts 1 O 2 molecules at the level of 1.2 × 10 8 to 2.0 × 10 9 per cell upon exposure to high energy (6 MeV) radiation with a radiotherapeutic dose of 60 Gy.…”
Section: Depth Penetrationmentioning
confidence: 97%
“…These values are comparable to the threshold for tumor spheroids by 1 O 2 species (~2 × 10 8 molecules per cell) as literature reported. [21] …”
mentioning
confidence: 99%
“…X-ray-excited PDT, based on scintillating nanoparticles, was first introduced by Chen and Zhang [12] in 2006 and recently several studies have demonstrated this effect into proof of concept [8, 1315]. For future clinical applications, the photosensitizers can be loaded onto nanoparticles, which can lead to a more direct and specific localization of the photosensitizer to the brain tumor sites and increase the efficiency and selectivity in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although scintillating nanoparticles have been studied in PDT [13, 15, 18], to the best of the authors’ knowledge, the non-invasive PDT concept of using scintillating nanoparticles in brain cancer cells has not been described.…”
Section: Introductionmentioning
confidence: 99%